Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1051/0004-6361/201935577
|View full text |Cite
|
Sign up to set email alerts
|

The Close AGN Reference Survey (CARS)

Abstract: The [C II]λ158 μm line is one of the strongest far-infrared (FIR) lines and an important coolant in the interstellar medium of galaxies that is accessible out to high redshifts. The excitation of [C II] is complex and can best be studied in detail at low redshifts. Here we report the discovery of the highest global [C II] excess with respect to the FIR luminosity in the nearby AGN host galaxy HE 1353−1917. This galaxy is exceptional among a sample of five targets because the AGN ionization cone and radio jet d… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 41 publications
2
9
0
Order By: Relevance
“…However, for the case of [C II], the discrepancy is mainly driven by LARS 5, a galaxy that is known to have a large scale outflow (Duval et al 2016). Our finding is thus in agreement with other studies (Appleton et al 2013(Appleton et al , 2018Smirnova-Pinchukova et al 2019) that reported on excess [C II]158 µm emission due to shocks connected to out flowing gas. Excluding LARS 5, the [C II] prescription of De Looze et al (2014) leads to SFRs that are only ∼80% higher.…”
Section: Metallicity-dependent Co-to-h 2 Conversionsupporting
confidence: 94%
See 1 more Smart Citation
“…However, for the case of [C II], the discrepancy is mainly driven by LARS 5, a galaxy that is known to have a large scale outflow (Duval et al 2016). Our finding is thus in agreement with other studies (Appleton et al 2013(Appleton et al , 2018Smirnova-Pinchukova et al 2019) that reported on excess [C II]158 µm emission due to shocks connected to out flowing gas. Excluding LARS 5, the [C II] prescription of De Looze et al (2014) leads to SFRs that are only ∼80% higher.…”
Section: Metallicity-dependent Co-to-h 2 Conversionsupporting
confidence: 94%
“…4 and 6. We note that shock-enhanced [C II]158 µm excess was previously observed in other galaxies with outflows (Appleton et al 2013(Appleton et al , 2018Smirnova-Pinchukova et al 2019).…”
Section: Extreme [C Ii]158 µM Line Strength In Lars 5 and Basic Pdr A...supporting
confidence: 73%
“…There is thus a mild average [CII] excess in the most luminous sources of our sample. Even if it is rare, [CII]-excesses have been observed in the local Universe (Smirnova-Pinchukova et al 2019), but we usually observe a deficit in bright sources (Díaz-Santos et al 2013). This apparent [CII] excess could also be an SED effect.…”
Section: Obscured Sfr As a Function Of [Cii] Luminositymentioning
confidence: 68%
“…Evidence of excess C + with respect to the maximum line cooling efficiency expected from pure photo-dissociation regions has been seen in purely star-forming galaxies at z 1-2 (Brisbin et al 2015). In the local Universe, Seyfert galaxies hosting powerful AGNdriven radio jets and winds inject turbulence into the surrounding ISM, contributing to the excitation of a larger mass of the C + reservoir (Guillard et al 2015;Appleton et al 2018;Smirnova-Pinchukova et al 2019) (in contrast with the depletion scenario based on ionization described above, from Langer & Pineda 2015). In addition, low velocity shocks driven by galaxy collisions can also turbulently heat the gas on large scales in dense environments (Appleton et al 2013(Appleton et al , 2017.…”
Section: What Emission Is the Smbh In Extremely Luminous Hotmentioning
confidence: 99%